Functional systemic approach to the resuscitation and intensive care - Sadchikov D.V. (Саратовский научно-медицинский журнал, 2014)
Functional systemic approach to the resuscitation and intensive care may be considered as a direct correlation between analysis and synthesis, induction and deduction, and, in general, between the formal and dialectical categories. The realization of this system should be started with the interaction and formation of the final beneficial result. Therefore the experience assessment on the basis of functional systematic approach will enable us to formulate more precisely the subject and methods of resuscitation from the philosophical point of view taking into consideration the interaction of the human life integrity with death phenomenon as fixed in ontogenesis and will allow to methodically justify the distinguishing of functional systems and standard processes both in sanogenesis and thanatogenesis.